Evolutionary Tracks of Chromosomal Diversification in Surgeonfishes (Acanthuridae: Acanthurus) Along the World’s Biogeographic Domains - Fernandes, Maria Aparecida; Cioffi, Marcelo de Bello; Bertollo, Luiz Antônio Carlos; Costa, Gideão Wagner Werneck Félix da; Motta-Neto, Clóvis Coutinho da; Borges, Amanda Tôrres; Soares, Rodrigo Xavier; Souza, Allyson Santos de; Pinthong, Krit; Supiwong, Weerayuth; Tanomtong, Alongklod; Molina, Wagner Franco (Frontiers in Genetics, 2021)
Fishes of the genus Acanthurus (Acanthuridae) are strongly related to reef environments, in a broad biogeographic context worldwide. Although their biological aspects are well known, cytogenetic information related to this genus remains incipient. In this study, Acanthurus species from populations inhabiting coastal regions of the Southwest Atlantic (SWA), South Atlantic oceanic islands (Fernando de Noronha Archipelago and Trindade Island), Greater Caribbean (GC), and Indo-Pacific Ocean (the center of the origin of the group) were analyzed to investigate their evolutionary differentiation. For this purpose, we employed conventional cytogenetic procedures and fluorescence in situ hybridization of 18S rDNA, 5S rDNA, and H3 and H2B-H2A histone sequences. The Atlantic species (A. coeruleus, A. chirurgus, and A. bahianus) did not show variations among them, despite their vast continental and insular distribution. In contrast, A. coeruleus from SWA and GC diverged from each other in the number of 18S rDNA sites, a condition likely associated with the barrier created by the outflows of the Amazonas/Orinoco rivers. The geminate species A. tractus had a cytogenetic profile similar to that of A. bahianus. However, the chromosomal macrostructures and the distribution of rDNA and hisDNA sequences revealed moderate to higher rates of diversification when Acanthurus species from recently colonized areas (Atlantic Ocean) were compared to A. triostegus, a representative species from the Indian Ocean. Our cytogenetic data covered all Acanthurus species from the Western Atlantic, tracked phylogenetic diversification throughout the dispersive process of the genus, and highlighted the probable diversifying role of ocean barriers in this process.